2014
DOI: 10.7763/ijbbb.2014.v4.300
|View full text |Cite
|
Sign up to set email alerts
|

Removal of Chromium (VI) by Bacillus subtilis Isolated from East Calcutta Wetlands, West Bengal, India

Abstract: Abstract-Chromium (VI), one of the major pollutants released from tanneries, dye and textile industries, is highly toxic and carcinogenic in nature. Chemical methods for bulk treatment of industrial effluents often fail to reduce the level to meet the environmental regulations. For end of the pipe treatment, bioremediation is considered a better alternative. East Calcutta Wetlands, the major sewage treatment site of Kolkata (previously known as Calcutta), has been reported to be contaminated with several heav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 13 publications
1
4
0
Order By: Relevance
“…Earlier reports have shown such properties exist in these bacteria (Zhao et al, 2012) and thus further validate our study. Apart from these, Bacillus subtilis has also been shown to exhibit certain keratinolytic properties (Pillai et al, 2011) with chromium reducing efficiency (Basu et al, 2014). The keratinolytic activity shown by IS4 (B. brevis) was also previously reported particularly concerning chicken feathers which also correlates nicely with our present findings (Jaouadi et al, 2017).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Earlier reports have shown such properties exist in these bacteria (Zhao et al, 2012) and thus further validate our study. Apart from these, Bacillus subtilis has also been shown to exhibit certain keratinolytic properties (Pillai et al, 2011) with chromium reducing efficiency (Basu et al, 2014). The keratinolytic activity shown by IS4 (B. brevis) was also previously reported particularly concerning chicken feathers which also correlates nicely with our present findings (Jaouadi et al, 2017).…”
Section: Discussionsupporting
confidence: 91%
“…Hence, it becomes clear that the efficient removal of toxic pollutants from the tannery effluents before their discharge to the natural waterways can be accomplished utilizing a sustainable, costeffective, eco-friendly, and easy-to-apply green technology such as bioremediation (Fernández et al, 2018;Vijayaraj et al, 2018). Interestingly, much work has not been done regarding isolation or identification of novel bioremediators from Kolkata, West Bengal except for a few reports (Basu et al, 2014). Also owing to the different biogeochemical scenarios prevailing in different parts of India, the microbes used for bioremediation in areas like Chennai may not be suitable for use in Kolkata due to climatic diversification of these two places.…”
Section: Discussionmentioning
confidence: 99%
“…Chromium contamination and damages caused by its input to several ecosystems have generated studies on bioremediation, using the ability of some microorganisms to concentrate metals diluted in aqueous solutions, storing them in their cellular structure, i.e. yeast, fungi, algae and bacteria (Basu et al 2014, Duca et al 2012. Ilias et al (2011) reported that isolates of Staphylococcus aureus and Pediococcus pentosaceus can grow on 2,000 mgL -1 Cr(VI) (as K 2 Cr 2 O 7 ) in Luria-Bertani (LB) medium; Pal & Paul ( 2004) described a group of 34 chromiumresistant bacteria isolated from naturally occurring chromium percolated serpentine soil able to reduce chromate under aerobic conditions, and one of this isolates Bacillus sphaericus was tolerant to 800 mgL -1 Cr(VI) and reduced 80% Cr(VI) during growth; Duca et al (2012) evaluated the ability of Aspergillus niger BM-56 to remediate Cr(VI) solutions obtaining a removal efficiency of 100% at different metal concentrations (0.1; 0.5 and 1.0 mgL -1 ) and pH (2.5; 4.5; 5.5 and 7.0).…”
Section: Introductionmentioning
confidence: 99%
“…Monod derivatives with substrate inhibition adjustment Eqs. ( 24 and 32 ), suggested by the Haldane, Aiba–Edward, Luong, Han, and Levenspiel models, have been used to assess the impacts of inhibition at a high substrate concentration and stimulation at a low concentration of substrate 71 74 . Here, S and μ are the substrate concentration and the specific growth rate, respectively; μmax is the maximum specific growth rate; n and m are experimental constants; Ks is the half substrate saturation coefficient, and Sm is the critical inhibitor concentration (mg/L) above which growth ceases.…”
Section: Resultsmentioning
confidence: 99%